Analysis of Pelangi Mart Employee Performance in terms of Leadership and Work Environment with Job Satisfaction as a Mediator Variable - Sinollah, Sinollah; Sudarmiatin, Sudarmiatin; Ludi Wishnu Wardhana (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to determine and analyse the effect of leadership and work environment on job satisfaction and its impact on Pelangi Mart employees' performance either directly or indirectly. To answer these objectives, this research uses quantitative research with questionnaires as the main data collector with 93 employees. The data analysis used is path analysis. The results showed that: (1). Leadership has a significant effect on job satisfaction; (2). The work environment has no significant effect on job satisfaction; (3). Job satisfaction has a significant effect on employee performance; (4). Leadership has no significant effect on performance; (5). Work environment has no effect on employee performance; (6). Leadership has a significant effect on performance through employee job satisfaction, and (7) the work environment has no significant effect on performance through employee job satisfaction. For this reason, Pelangi Mart management in improving employee performance in terms of leadership must pay attention to employee job satisfaction.